Reconciliation through language learning? A case study of the Turas Irish language project in East Belfast - Mitchell, David (My University, 2019)
Language is frequently present in the conflictual symbolic politics of violent inter-group conflict. In Northern Ireland, the Irish language has long been contested and has been drawn into the maelstrom of cultural conflict since the 1998 Good Friday Agreement; hence the improbability of an Irish language learning/teaching initiative, operating since 2011, based in Protestant, pro-British East Belfast. This article offers the first academic analysis of the “Turas” project, focusing on understanding its reconciliation contribution. Firstly, the article examines why language is so often contested in identity group competition. Secondly, findings of qualitative research inside Turas regarding the means and meanings associated with the project are reported. Thirdly, drawing on the case study, the article argues that language learning offers three distinct reconciliatory opportunities: revising destructive understandings of history; challenging exclusivist territorializations of group memory; and facilitating critical reflection on self, and empathy for other.
PUBLISHED
Keywords: Northern Ireland; Reconciliation; Language; Conflict; Turas; Irish language; Identities in Transformation; Inclusive Society; Northern Ireland Conflict; Peace Studies